The Effect of the SrVER Model Assisted by Virtual Reality (VR) Media on Biology Learning Outcomes of 10th Grade Students at SMAN 3 Mataram - Maryam, Natasya Oktavianil; Handayani, Baiq Sri; Lestari, Tri Ayu; Setiadi, Dadi (Journal of Classroom Action Research, 2025)
The difficulty in understanding abstract biological concepts, combined with the dominance of lecture-based methods, hinders student learning outcomes. Therefore, there is a need for innovative, experience-based methods to improve comprehension. This study aimed to determine the effect of the SrVER learning model assisted by Virtual Reality (VR) media on the biology learning outcomes of 10th-grade students at SMAN 3 Mataram. The research used a quantitative approach with a quasi-experimental method, specifically a pre-test post-test control group design. The population included 13 10th-grade classes, and purposive sampling was employed, resulting in 4 classes as the sample. Data were collected through surveys and tests, with data analysis conducted using ANCOVA supported by IBM SPSS Statistics 25. The result showed a significance value of 0.001 ≤ 0.05, indicating a significant effect of the SrVER learning model assisted by VR media on students' biology learning outcomes. The SrVER learning model assisted by VR media proved to be more effective than traditional methods, as evidenced by improved biology learning outcomes.